Pragmatic Analysis of Dialogue in Wednesday Season 2 : Interpreting Implied Meanings - Zikri, Anisa Sabrina; Tur, Ajar Pradika Ananta (Journal of English Teaching, Literature, and Applied Linguistics, 2026)
This study analyzes the pragmatic aspects of dialogue in Wednesday Season 2 with a focus on interpreting implied meanings conveyed through sarcasm, irony, and indirect speech. Using a descriptive qualitative method and the framework of Relevance Theory (Sperber & Wilson, 1986), the research examines selected dialogues to uncover how characters express meaning beyond literal language and construct complex social interactions. The findings show that sarcasm and irony are central to Wednesday Addams’s identity, functioning as tools of humor, defiance, and social critique. Indirect speech and mock politeness also reveal her resistance to authority and her distinct way of asserting individuality. Overall, the study concludes that pragmatic elements in the series play a crucial role in building character depth, enhancing narrative tone, and engaging the audience through layered, context-dependent communication that reflects both cognitive and emotional dimensions of meaning.